Pollution Profile of River Ganga - Kamal, K.P.; Singh, S.P.; Bhosle, A.K.S.; Mujtaba, S.G. (Asian Journal of Chemistry, 2010)
The monitoring of pollution status of river Ganga is very essentialand vital at intervals of every two years. It has been observedthat Ganga water maintains a uniform character throughout Mungerand Bhagalpur having high turbidity and alkalinity. However, hardnessis quite tolerable. The dissolved oxygen content ranging from6.5-7.7 ppm is quite favourable for aquatic life.